ANALISIS KERENTANAN BANJIR UNTUK KAJIAN MITIGASI BENCANA BANJIR DI KECAMATAN KAWUNGANTEN KABUPATEN CILACAP TAHUN 2013 - Karnilasari, Radita (Pendidikan Geografi, 2014)
The objectives of the research are to find out, analysis and describe (1) The level of flood vulnerability in Kawunganten sub district in the year of 2013, (2) The flood type in Kawunganten sub district in the year of 2013, (3) Flood hazard mitigation efforts in Kawunganten sub district in the year of 2013.Methods of the research used are spatial descriptive and geography concept of differentiation area. Analysis unit used is terrain unit. Technique of analysis data used for knowing the flood vulnerability by scoring each parameter. They are gradient, groundwater, soil texture, soil drainage, soil permeability. There is no scoring in parameter of land use, but it is analyzed is there any malfunction of land use and how far the effect towards flood vulnerability on each field. Technique of analysis data for knowing flood type by interviewing the society and department worker and analyzed based on the characteristic of each field by field survey. Technique of flood vulnerability analysis is suited with level of flood vulnerability and structure and non-structure mitigation is suited with flood type. Based on the result analysis, it can be concuded that (1) There are six terrain units in Kawunganten subdistrict. They are, Vegetated Tidal Flats, Alluvial Plain, Swamp, Flood Plain, Hills Sinklinal and Valley Sinklinal (2) There are four flood vulnerability level in Kawunganten, they are flood vulnerability in high level, medium level, low level, and non-vulnerable level (3) Kawunganten subdistrict has three flood type, they are local flood, coastal flood, flash flood (4) Flood hazard mitigation in Kawunganten subdistrict divides into three priority scales, they are priority I , priority II , and priority III.Keyword: Flood Vulnerability Level, Flood Type, Flood Hazard Mitigation